Understanding Why Scholars Hold Different Views on the Influences of Video Games on Public Health. (29th March 2017) - Ferguson, Christopher J.; Colwell, John
Abstract : Despite decades of research, no scholarly consensus has been achieved regarding the potential impact of video games on youth aggression or other public health concerns. In recent years, hypotheses have been raised that scholarly opinions on video games may resemble past moral panics, with attitudes reflective of generational conflicts. These hypotheses are tested in a sample of 175 criminologists, psychologists, and media scholars, examining both overall negative attitudes about video games and perceived linkages with youth assaults specifically. Results reflected continued lack of scholarly consensus on the issue of video game influences with only 15.3% of scholars endorsing the view that violent video games contribute to youth assaults. As hypothesized, older scholars endorsed more negative views of video games generally, although this appeared to be related to experience with games rather than age per se. Scholars with more negative attitudes toward youth themselves were also more negative about games. Criminologists and media scholars were more skeptical of violent video games contributing to youth assaults than were psychologists. These results are discussed in relation to Moral Panic Theory.